Strategi Pemberdayaan Usaha Mikro Kecil dan Menengah dalam Rangka Menyongsong Pasar Global - Rosmiati Rosmiati (Universitas Muhammadiyah Jambi, 2014)
The era globalization has challenged business to compete produce a quality product types. Once the importance of the role of bussines especially micro, small and medium enterprises (SMEs) in producing a product, it is necessary effors and right strategies for empowering micro, small and medium enterprises (SMEs). This study aims to develop a proper strategi to maximize and develop micro, small and medium enterprises (SMEs) and area need to be known and analyzed. The method in this study is a deskriptif study of literature review study discussed the strategi of empowering micro, small and medium enterprises (SMEs). The are three (3) basic policies needed in empowering micro, small and medium enterprises (SMEs), which are (1) creating a conducive bussinessenvironment at the same time providing an evirontment that encourages the development of SMEs syistemically, independent, and sustainable, (2) creating insurance system financially to the operation of productive economic activities undertaken by SMEs and (3) provide technical assistance and managerial assistance in order to improve th e status of SME. The conclusion of this literature review provide an important means for achieving planning appropriate strategies on micro, small and medium enterprises (SMEs).